Cry and Delight in Time of Pandemic: A Phenomenological Inquiry on the Experiences of Multi-grade Teachers in a Philippine Public Elementary School - Beleganio, Annaros B.; Madrigal, Dennis V. (Technium Social Sciences Journal, 2022)
Education does not only allow for the exploration of every aspect of life but as well as have a longing for knowledge and the desire to take this learning to the next level. Thus, the teacher’s role in the teaching and learning process is vital. However, that delivery of the instruction towards the learners is a big challenge for the teachers who are handling Multi-grade teaching in this new normal. Multi-grade teaching is a situation in which one teacher has to teach many grade levels, all at the same time. Thus, the paper explores the lived experiences of Multi-Grade Teachers in public elementary school in the time of pandemic. Aided by a phenomenological research approach, the data were gathered from purposively sampled participants using face-to-face and online interviews. The data were analyzed using thematic analysis devised by Lichtman. The findings reveal semblance in the participants’ views and practices in multi-grade teaching during the pandemic. Despite the detected adverse elements that relegate it, multi-grade teachers remain passionately dedicated to facilitating learning. However, making learners master the competencies required is still a great challenge to realize. Thus, the collaboration of all stakeholders, school administrators and local government are vital to address this perennial challenge in multi-grade teaching.